The T-cell antigen receptor regulates sustained increases in cytoplasmic free Ca2+ through extracellular Ca2+ influx and ongoing intracellular Ca2+ mobilization. - Imboden, J B (1987)
Signal transduction by the T-cell antigen receptor involves the turnover of polyphosphoinositides and an increase in the concentration of cytoplasmic free Ca2+ ([Ca2+]i). This increase in [Ca2+]i is due initially to the release of Ca2+ from intracellular stores, but is sustained by the influx of extracellular Ca2+. To examine the regulation of sustained antigen-receptor-mediated increases in [Ca2+]i, we studied the relationships between extracellular Ca2+ influx, the mobilization of Ca2+ from intracellular stores, and the contents of inositol polyphosphates after stimulation of the antigen receptor on a human T-cell line, Jurkat. We demonstrate that sustained antigen-receptor-mediated increases in [Ca2+]i are associated with ongoing depletion of intracellular Ca2+ stores. When antigen-receptor-ligand interactions are disrupted, [Ca2+]i and inositol 1,4,5-trisphosphate return to basal values over 3 min. Under these conditions, intracellular Ca2+ stores are repleted if extracellular Ca2+ is present. There is a tight temporal relationship between the fall in [Ca2+]i, the return of inositol 1,4,5-trisphosphate to basal values, and the repletion of intracellular Ca2+ stores. Reversal of the increase in [Ca2+]i preceeds any fall in inositol tetrakisphosphate by 2 min. These studies suggest that sustained antigen-receptor-induced increases in [Ca2+]i, although dependent on extracellular Ca2+ influx, are also regulated by ongoing inositol 1,4,5-trisphosphate-mediated intracellular Ca2+ mobilization. In addition, an elevated concentration of inositol tetrakisphosphate in itself is insufficient to sustain an increase in [Ca2+]i within Jurkat cells.